2001
DOI: 10.1038/oby.2001.64
|View full text |Cite
|
Sign up to set email alerts
|

Hyperphagia as a Mediator of Renal Disease Initiation in Obese Zucker Rats

Abstract: Objective: We sought to determine whether prevention of overeating would block the very earliest manifestations of renal injury in young obese Zucker rats (OZRs). Research Methods and Procedures: Three groups of rats were studied, obese (fa/fa) Zucker rats and lean (Fa/Fa). Zucker controls were allowed to feed ad libitum, whereas a group of obese (fa/fa) Zucker rats was pair-fed to the lean group. Urine albumin and serum lipids were studied weekly from 6 to 10 weeks of age. Renal pathology and renal glomerular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
26
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 34 publications
2
26
0
Order By: Relevance
“…These rats have impaired glucose tolerance and increased blood glucose levels, endothelial dysfunction, and die of renal failure [5][6][7][8][9]. The mechanisms responsible for renal injury in syndrome X patients and the obese Zucker rats are not well understood.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…These rats have impaired glucose tolerance and increased blood glucose levels, endothelial dysfunction, and die of renal failure [5][6][7][8][9]. The mechanisms responsible for renal injury in syndrome X patients and the obese Zucker rats are not well understood.…”
Section: Introductionmentioning
confidence: 96%
“…life [5][6][7][8][9]. These rats have impaired glucose tolerance and increased blood glucose levels, endothelial dysfunction, and die of renal failure [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 97%
“…ZUC either homozygous or heterozygous for the wildtype allele ( Lepr + or Lepr faSte/+ ) are lean and are designated lean ZUC in this paper. Previous studies of ZUC rats also reported that hyperphagia and hypertriglyceridemia accelerate renal disease [4], [5]. However, studies comparing lean and obese ZUC rats cannot distinguish between effects caused by obesity due to the chromosome 4 Lepr mutation from those caused by an interaction of Lepr with specific alleles from other chromosomes such as obesity-dependent renal and type 2 diabetes alleles.…”
Section: Introductionmentioning
confidence: 98%
“…ZUC rats exhibit many other traits including renal disease and Type 2 diabetes (7,10,13). Renal disease in Zucker rats is accelerated by hyperphagia and is correlated with hypertriglyceridemia (7,21).…”
mentioning
confidence: 99%